Properties of several soils cultivated with cocoa in the province of El Oro, Ecuador - Barrezueta-Unda, Salomón (Universidad Autónoma de Tamaulipas, 2019)
The physical and chemical properties of the soil, as a whole, condition the productive capacity of the plants. The research aimed to characterize the properties of the main cocoa soils in theprovince of El Oro (Ecuador), in the municipalities of El Guabo, Machala, Sata Rosa and Pasaje. We selected 30 plots of cocoa types CCN51 (n = 18) and National (n = 12), from which soilsamples from 0 cm to  30 cm were extracted to analyze various physical and chemical properties in the laboratory. The results showed no significant differences (P >0.05) between thephysical properties. The carbon levels, ranged from 1.58 % (El Guabo) to 2.06 % (Santa Rosa). In general, the nitrogen was low (0.16 % a 0.18 %). The values of: CE (0.13 13 dS/m to -0.21 dS/m), pH (6.46 to 7.72), CIC (23.4040 cmol/kg to -43.86 cmol/kg), potassium (0.310.31 cmol/kg to -1.86 cmol/kg) and calcium (19.99 cmol/kg to -37.73 cmol/kg) tended to be higher in Machala soils(< 0.05) and lower in Pasaje soils. The soils of Santa Rosa had higher concentrations of copper (16.6 mg/k) (P < 0.05) than in the rest of the municipalities. Cocoa yield CCN51 (2 570.24 kg/ha/y to 4 158.34 kg/ha/y) was higher than National (324.00 kg/ha/y to 814.17 kg/ha/y). The soils of Machala presented higher nutritional values, associated with higher average yield forNational variety cocoa, and a high yield for CCN51 variety.